Quantifying spatial patterns of urbanization: growth types, rates, and changes in Addis Ababa City from 1990 to 2020 - Busho, Seifu Woldemichael; Wendimagegn, Getinet Teshome; Muleta, Alexander Takele (Spatial information research (Online), 2021)
Urban patterns have shown that shifts in the social, economic, and geographical features of an area result in metropolitan growth, planned or otherwise. Rapid urbanization takes a toll on the ecological makeup of the environment and the wellbeing of humans at multiple levels. Thus, this study was drafted to quantify urban growth rates, types, and changes, with regards to urbanization patterns from 1990 to 2020. It tries to evaluate whether Addis Ababa’s urban expansion conforms to the diffusion-coalescence theory using remote sensing data. The Spatio-temporal pattern and changing aspects of the built-up land were examined using urban growth types, spatial metrics, and a gradient method. The last decade evidenced the most pronounced growth within a buffer distance of 10 to 22 km from the city center. Edge expansion was the most dominant form of growth across all three decades with more than 61% of new development each. Infill and outlying growth showed decadal variability with an alternating dominance. The Spatio-temporal investigation confirmed that the urban class and growth types remained consistent. The team concluded that diffusion and coalescence are two simultaneously occurring phases of urban growth rather than two dichotomous successive phases. Spatio-temporal patterns and the dynamic behavior of spatial metrics are instrumental in comprehending the urban growth process and cycle. Moreover, the results can aid in assessing the land use planning policy as well as to guide future land use planning.